Hydrothermal carbonization coupled with pyrolysis: An innovative approach to digestate management - Ziyi Shi; Sirui Liu; Shule Wang; Lukasz Niedzwiecki; Marcin Baranowski; Michał Czerep; Chuchu Tang; Sibudjing Kawi; Chi-Hwa Wang; Jianchun Jiang; Mikael S. Hedenqvist; Halina Pawlak-Kruczek; et al. (Green Energy and Resources, 2023)
Anaerobic digestion presents a viable approach for managing biodegradable waste. However, the process generates a significant amount of digestate, which, if not appropriately managed, can contribute to eutrophication and salinization. This research explores the integration of hydrothermal carbonization (HTC) and pyrolysis as a potential solution for digestate management, emphasizing volume reduction and energy recovery. The study specifically focuses on the production of biochar from agricultural waste digestate (AWD) in an energy-efficient manner. Utilizing HTC as a pretreatment was found to enhance the heating value of both the AWD and the subsequent pyrolytic char, and it also improved the carbonization degree of the resulting char. Energy balance analysis revealed that the pyrolysis of AWD shifted from an endothermic to an exothermic reaction upon HTC pretreatment. This transition decreased the reaction's energy absorption from 41.1 to 1557.6 MJ to an energy release of 685.1 to 960.6 MJ per ton of digestate, thereby optimizing energy consumption in digestate management. Additionally, it was noted that using acetone as a solvent in gas chromatography for biooil samples with high ammonia content led to the formation of diacetonamine, an outcome that is deemed undesirable.